2022
DOI: 10.3390/admsci13010011
|View full text |Cite
|
Sign up to set email alerts
|

The Epic Game of Creating a Successful Gamified Co-Creation Strategy

Abstract: This paper aims to explore consumer engagement with online retailers through gamification, the use of game mechanics, and co-creation. A qualitative methodology was used through an exploratory case study approach. The interviews were conducted with 30 Portuguese consumers. It was found that the majority of respondents do not consider online shopping as a substitute for other entertainment activities. Respondents stressed that in online shopping, the important thing is personal satisfaction and their needs. Acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
(114 reference statements)
0
0
0
Order By: Relevance
“…Gamification has features that encourage customers to do the activities that companies expect from them and enhance value co-creation. In addition, studies by Leclercq et al (2018), Qian et al (2022) and Lopes et al (2022b) showed that one of the main outcomes of gamification is to engage customers and improve customer value co-creation behavior in online communities. In a study conducted on an e-commerce platform by Xu et al (2022), they found that gamification affordances and psychological ownership as one of the main aspects of value co-creation can positively impact customer citizenship behavior.…”
Section: Theoretical Foundation and Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Gamification has features that encourage customers to do the activities that companies expect from them and enhance value co-creation. In addition, studies by Leclercq et al (2018), Qian et al (2022) and Lopes et al (2022b) showed that one of the main outcomes of gamification is to engage customers and improve customer value co-creation behavior in online communities. In a study conducted on an e-commerce platform by Xu et al (2022), they found that gamification affordances and psychological ownership as one of the main aspects of value co-creation can positively impact customer citizenship behavior.…”
Section: Theoretical Foundation and Literature Reviewmentioning
confidence: 99%
“…Active customer engagement is critical to the successful implementation of co-creation. Lusch et al (2012) examined value co-creation that occurs when customers engage in spontaneous behavior beyond predefined choices. In this approach, consumers and firms proactively share resources such as skills, knowledge, time, capital and technology (Cova et al, 2015).…”
Section: Theoretical Foundation and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation